Partner Power: A study of two distance education consortia - Pidduck, Anne Banks; Carey, Tom (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2006)
This research reports findings from a study which explored the process and criteria of partner selection – how and why partners are chosen – for two distance education consortia. The researchers reviewed recent literature on partnerships and partner selection. Two Canada-wide distance education consortia were identified as large-scale case studies for investigation of the research theory. A total of 34 informants were contacted. Written business plans, contracts, documents, partner network diagrams, and 231 archival emails from 36 correspondents were collected and analyzed for the two consortia. The research identified four criteria that influence why specific partners are chosen: requirements, resource availability, social network, and reputation. These findings suggest that the formation of partnerships and the process of partner selection are both very complex.